Sharia mutual funds performance in Indonesia - Robiyanto Robiyanto; Michael Alexander Santoso; Rihfenti Ernayani (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The study aims to measure each Sharia mutual fund performance and compare with market performance in Indonesia. Sharia mutual fund investment instruments in Indonesia have positive developments over the period from 2012 to 2017. These positive developments add to the option of investment instruments for public, especially investors who put forward the principles of Sharia. This research was conducted so that the public could have scientific information about Sharia mutual funds that have the best performance. The study found consistent results regarding Sharia mutual funds with the best performance on Sharpe and Jensen measurement methods. The best performing Sharia mutual fund by using those methods was PNM Syariah, while the lowest-performing mutual fund was PNM Amanah Syariah if measured by using Sharpe Index and PNM Ekuitas Syariah if measured by using Jensen Alpha. Different results were found when Sharia mutual fund performance was measured using Treynor Ratio Information Ratio, where the best Sharia mutual fund performance was by Manulife Syariah Sectoral Amanah mutual fund while the lowest performance was by Cipta Syariah Equity mutual fund. This findings are expected to be useful for Sharia-based investors.
Keywords: G11; 650; Sharia mutual fund; Jensen Index; Sharpe Index; Treynor Ratio; Information Ratio